2022
DOI: 10.31480/2330-4871/152
|View full text |Cite
|
Sign up to set email alerts
|

Dezocine is a Biased Ligand without Significant Beta-Arrestin Activation of the mu Opioid Receptor

Abstract: Dezocine is an opioid that was used in clinical practice for acute pain management in the US (1986US ( to 2011 and is currently in use in China. It is not listed as a controlled substance in the US due to no reported cases of addiction. Dezocine is a partial agonist at the mu opioid receptor (MOR); however, it is unclear whether dezocine can activate both the G protein pathway and the beta-arrestin pathway. In this study we hypothesized that dezocine does not activate the beta-arrestin pathway, which could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In the future drug development for addiction therapy, short‐acting regimen for an easy taper down or taper off opioids should be explored. We and others have found that dezocine, a previously FDA approved opioid, is a potential candidate for such purposes (Dalgan, average half‐life 2.2 h) 10–13 . It was discontinued in the US market around 2011 following its substance matter patent expiration.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In the future drug development for addiction therapy, short‐acting regimen for an easy taper down or taper off opioids should be explored. We and others have found that dezocine, a previously FDA approved opioid, is a potential candidate for such purposes (Dalgan, average half‐life 2.2 h) 10–13 . It was discontinued in the US market around 2011 following its substance matter patent expiration.…”
mentioning
confidence: 99%
“…Unlike other opioids, there are no reports in the English language medical literature of addiction or abuse or associated death with dezocine despite decades of clinical usage. It is a partial mu opioid receptor (MOR) agonist without significant beta‐arrestin pathway activation and is a kappa opioid receptor antagonist 13,14 . It also inhibits both norepinephrine and serotonin transporter proteins, comparable to nisoxetine, an anti‐depressive medication with analgesia properties 14 .…”
mentioning
confidence: 99%
See 2 more Smart Citations